PENERAPAN ELECTRONIC GOVERNMENT DI KANTOR PENGADIAN AGAMA KOTA PEKANBARU - Yenny Nurhidayah; Dadang Mashur (Cross-border, 2022)
Application Electronic Government at the Pekanbaru City Religious Court Office is implementation service public with use technology information and communication in give service to public for manifest in the Religious Courts of the Bureaucratic Region Clean and Serving (WBBM). However, on implementation application Electronic Governance this still there is the problem that becomes obstacles on implementation, such as Allocation Source power humans who haven't equally and lack of sustainable socialization. Study this aim for knowing Application Electronic Governance at the Pekanbaru City Religious Court Office as well as factor the inhibitor. Draft the researcher 's theory use is E-Government theory by Indrajit with six indicator that is E-Strategy, Architecture, Risk and Program Management, Organizational Capabilities, Value Chain Management, and Performance Management. Study use method study qualitative with technique data collection based on interviews, observations, and documentation.The results of the research found are the application of Electronic Government at the Pekanbaru City Religious Court which has been carried out optimally, that the implementation of e-government provides convenience to the community.Inhibiting factors are the unequal allocation of human resources, lack of socialization and education, and network disturbances. So that it has an influence on the implementation of Electronic Government at the Office of the Religious Courts in Pekanbaru City.